(untitled) (Research, Society and Development, 2020)
The aim of this study was to estimate the population size of dogs and cats domiciled and semi-domiciled in the urban area of the city of Jataí, Goiás, Brazil, highlighting some features of these animals, like sex and mobility. An observational descriptive sample survey was used and households were randomly selected for the study. In total, 385 households were visited, with 1215 residents. Of the households, 63.63% had at least one dog and 11.17% had at least one cat. The dog: human ratio was 1:2.92 and cat: human ratio was 1:11.79. In relation to the canine population (416), 37.02% were male (5.29% neutered and 31.73% non-neutered) and 62.98% were female (9.37% neutered and 53.60% non-neutered). The feline population was 103 animals, 39.80% were male (14.60% neutered and 31.47% non- neutered) and 46.60% were female (18.86% neutered and 37.08% non-neutered). In relation to street access, 32.93% of dogs and 84.46% of cats were semi-domiciliary. The estimated population of canines and felines domiciled and semi-domiciled in the urban region of the city of Jataí, in 2018, was 3.605 and 8.323, respectively. These results highlight the need to implement strategies for population control associated with actions to raise awareness about responsible animal custody.